2022
DOI: 10.1186/s12894-022-01074-9
|View full text |Cite
|
Sign up to set email alerts
|

Expression and prognostic value of carbonic anhydrase IX (CA-IX) in bladder urothelial carcinoma

Abstract: Objective To investigate the expression intensity of carbonic anhydrase IX (CA-IX) in bladder urothelial carcinoma and its predictive value for the recurrence after transurethral resection of bladder tumor. Methods A retrospective analysis was made of 194 specimens who underwent transurethral resection of bladder tumors in our hospital from January 2014 to January 2016 and completed follow-up. The expression intensity of CA-IX and the clinical data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…These pH regulators, such as CAIX, may also play a role in the cells’ sensitivity to AZD3965. CAIX is overexpressed in UBC and has been associated with high recurrence rates [ 60 , 61 ]; it seems to facilitate monocarboxylate transportation by binding to CD147, thus enhancing MCT1/4 activity [ 62 ]. Thus, although AZD3965 may decrease lactate exportation through MCT1 targeting, this may not result in a significant decrease in intracellular pH due to CAIX interference in the pH balance.…”
Section: Discussionmentioning
confidence: 99%
“…These pH regulators, such as CAIX, may also play a role in the cells’ sensitivity to AZD3965. CAIX is overexpressed in UBC and has been associated with high recurrence rates [ 60 , 61 ]; it seems to facilitate monocarboxylate transportation by binding to CD147, thus enhancing MCT1/4 activity [ 62 ]. Thus, although AZD3965 may decrease lactate exportation through MCT1 targeting, this may not result in a significant decrease in intracellular pH due to CAIX interference in the pH balance.…”
Section: Discussionmentioning
confidence: 99%
“…Bladder cancer, similarly to other malignancies, exhibits this glycolytic phenotype (reviewed in [16][17][18]). Several studies reported significant associations between aggressive tumor features and poor prognosis, and the upregulation of glucose transporters [19], glycolytic enzymes and their downstream players [20][21][22][23][24], pH regulators [25], and lactate transporters [26,27]. Genetic and/or pharmacological inhibition of these molecules suppressed aerobic glycolysis, cell proliferation, migration and invasion in vitro and tumor growth in vivo [20,23,24,[28][29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%